Optimization of the composition of polysaccharide-based composite films as a potential food packaging material - T. V. Kryuk; T. G. Tyurina; O. S. Popova; N. A. Romanenko; G. P. Goncharuk; E. N. Trush (Пищевые системы, 2025)
The development of biodegradable food packaging based on renewable natural raw materials is one of the key trends of modern research worldwide. It is possible to obtain film materials for food packaging on the basis of corn starch and sodium carboxymethyl cellulose provided that small amounts of polyvinyl alcohol (PVA), citric acid (CA) and glycerol (Gl) are added to the polymer composition. The paper presents the results of the composition optimization of such films using the response surface methodology. The influence of independent variables (PVA concentration: 7, 10 and 15.5; CA concentration: 5, 7 and 9; Gl concentration: 20, 25 and 50 % in relation to the polysaccharides weight) on the response variables (swelling degree, gel fraction, water vapor transmission rate, tensile strength, elongation at break and Young’s modulus) is evaluated. The sample of the optimized composition (15.5 wt. % PVA, 7 wt. % СА and 37.5 wt. % GL) has good barrier and strength properties. Theoretical calculations based on the regression model demonstrated a high correlation with the experimental data. It is shown that the inclusion to the polymer matrix of additional components (antioxidants, reinforcing agents) will improve the operational characteristics of film materials and expand their functionality.